PENGARUH MEDIA DIGITAL STORYTELLING TERHADAP DAYA INGAT SISWA PELAJARAN SEJARAH KEBUDAYAAN ISLAM KELAS VII MTS - Ardhiana, Nisa; Anshori, Sholihul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is centered around a fundamental shift in how digital native generations handle information, as they exhibit a preference for technology-driven interactive learning. Digital storytelling is introduced to transform abstract historical content into a more concrete and understandable format. This study aims to explore the use of this medium and to analyze students' memory, and assess its impact on the subject of Islamic Cultural History at MTs Ar-Rahman. Using a qua quantitative approach with a nonequivalent control grop design, this study involved 51 seventh grade students selected from the total sample. Data were collection through observation, tests, and documentation and then analyzed using an Independent Sample T-Test and Effect Size using SPSS 27. The results of the indicate that digital storytelling is effective, as evidenced by students’ enthusiasm and active participation. Empirically, the experimental class achieved an average score of 74.31 (88.5% mastery), exceeding the control class, which scored only 67.84 (60% mastery). The results of the T-test indicate that digital storytelling has a significant effect on student memory in the moderate category, as evidenced by a significance value of 0.030 (less than 0.05) with a Cohen’s d of 0.626.